The relationship between erp training and its usage in management accounting activities: a study on SMEs in Malaysia / Emmarelda Maswesi Ahmad - Ahmad, Emmarelda Maswesi (2015)
Currently, there is a high demand for the Enterprise Resource Planning (ERP) systems among small to medium to sized companies in Malaysia. Due to the rapidly changing business environment, many organisations require the ERP system to integrate information from all departments and to support business activities. ERP is a necessity for every business to remain sustainable and competitive in the industry. The main objective of the study is to discover the relationship between ERP user training and ERP system usage in management accounting activities. The management accounting activities here refer to Capital Budgeting, Budgeting, Activity Based Costing, Operating Statement and Reporting and Forecasting. In addition, the second objective of the study relates to examining the relationship between ERP user training and company performance. Data was collected by means of online questionnaire in order to evaluate how training on ERP has made an impact on the usage of ERP system in the five management accounting functions and company performance. In general, the results indicate that ERP user training and the usage of ERP has enhanced the quality of management accounting practices. However, there was no indication to show that there was a significant relationship between ERP user training and company performance. Therefore, it can also be concluded that ERP system has an impact on the above mentioned management accounting practices. It is hoped that the findings of this study will offer substantial benefits to management accountants in performing their roles and responsibilities, contribute to the emerging list of literature on ERP systems and potential impact on management accounting education and research, and also to serve as an advantage to IT systems consulting companies in their effort to promote an effective ERP system user training.